Effect of simulation-based training workshop on obstetric emergency team collaboration and communication: a mixed study - Wu, Na; Li, Wei; Huang, Rong; Jiang, Hui (Frontiers in Medicine, 2024)
Aims and objectives To explore the effects of simulation-based midwife training workshops and determine whether such a program can improve team collaboration and communication. Background Simulation training improves communication, team cooperation, critical thinking, and situational awareness. Design This mixed study was conducted September 15–18, 2021. Methods Participants included 23 obstetricians and midwives who completed 2 days of simulation training, including communication, skills, teamwork, single technical operation, and scene running. The Clinical Teamwork Scale was used before and after the comparison, and the data were analyzed using a phenomenological analytic process. Results The total team cooperation, transparent thinking, closed-loop communication, overall decision-making, clear responsibility, and leadership scores of the trainees were significantly higher after than before the training. The experience of attending a simulated training workshop can be divided into two themes: innovative ways of offering training and active learning. Three key themes emerged from each category: education combined with recreation; full participation in interactions; and teamwork and communication. (1) application of knowledge (2) dissemination, and (3) sublimation of knowledge. Conclusion This study’s findings indicated a good experience and higher team cooperation score among midwives participating in simulation-based training in China, the value of our work is to show that the researched teaching methods, although published in other contexts, are also valuable in the Chinese context, suggesting that they will pass on the methods and concepts of the simulated training to others and change the current status of classroom teaching, which is its most meaningful practical training effect. Relevance to clinical practice These results imply that simulation-based midwife training for obstetric emergencies is required to improve the comprehensive ability of midwives to address obstetric emergencies, thereby improving maternal clinical outcomes. No patient or public contribution Neither patients nor the public were involved in this study, and the midwives and obstetricians voluntarily participated.